(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The drawbacks are that the concrete has been improved by using hybrid fibre in concrete. By hybridization benefits from two different fibres are utilized in a single concrete mixture. The hybrids fibres studied are basalt-polypropylene fibre, polypropylene-steel fibre, steel coconut fibre, polypropylene-e-waste fibre, polypropylene polyvinyl Alcohol and steel-glass- polypropylene fibre. The properties that are improved using hybrid fibres are compressive strength, tensile strength, flexural strength, limited crack propagation, and improved durability of the concrete structure. In maximum cases slump value decrease with an increase in fibre percentage.